Electrical Safety System on Ice Tube Machine - Yuli Prasetyo (International Journal of Science, Engineering, and Information Technology, 2022)
Ice is one of the products produced by cooling machines that can be used to lower the temperature. It is obtained from the process of changing the state of water into ice by cooling below the freezing point of water at 0Â°C. The process of cooling into ice is done by releasing heat energy which causes the surface of the water to harden. The use of ice-making technology can be done with the Smart Relay-based Fast Freezing Method. This method minimizes the manual system mechanism to increase ice production, one of which is Tube Ice. This research uses an experimental approach method to get the best results which will later be included in the PLC (Program Logic Controllers) and HMI (Human Machine Interface) systems in one Autonic Fort component. This research output is in the form of a smart tube ice machine (ice crystal). This ice machine can help the community in the culinary and fishery fields. With this tube ice machine, culinary entrepreneurs can get an ice supply quickly and hygienically. In contrast to the beam industry, which requires a large area and a lot of infrastructure. This smart tube ice machine can increase the productivity of the tube ice produced. This tube ice machine uses a design with a model and size that is very compact and easy to operate, does not require a large place. So that they can work as micro, small and medium enterprises that can support the community's economy.